Between law and politics: the judicialization of international dispute settlement in the fields of security, trade and the environment - Aletta Mondré; Gerald Neubauer; Achim Helmedach; Bernhard Zangl (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2008)
Many international treaties regulate a variety of policy fields deeply influencing state's policy options. Moreover, multilateral treaties establishing international organizations and regimes often include provisions how to settle disputes over norm interpretation and treaty application. International dispute settlement mechanisms increasingly install judicial procedures in place of more traditional, diplomatic means. The resulting proliferation of international courts and tribunals has sparked a lively debate about an (emerging) international rule of law. International rule of law would significantly alter the structure of international relations, as law would become an important ordering principle of world politics. However, it is not yet clear whether or how these developments affect actual state behavior. From our point of view, it is entirely an empirical question what effect – and to what extent –judicialized dispute settlement have on states. Presenting results from a comprehensive research project this paper systematically investigates the behavior of OECD member countries in international disputes. We analyze state behavior in over 100 individual disputes in three issue areas of international relations (trade, security and environmental protection) and across time (1970s/1980s compared to the 1990s). Our data demonstrates as a general trend that OECD countries do in fact increasingly use and accept internationally agreed dispute settlement procedures. Nevertheless, important differences across issue areas prevail. While in international trade most disputes are indeed dealt with under the Word Trade Organization's dispute settlement procedure, in the field of international security many disputes are dealt with outside the relevant procedure of the United Nations Security Council. With regard to environmental protection, the use of the CITES (Convention on International Trade in Endangered Species) dispute settlement mechanism falls in between. We observe an overall trend towards judicialization of state behavior, but to different degrees in the different issue areas. – – Viele Sachbereiche der internationalen Politik werden durch internationale Verträge reguliert. Oftmals sind Verfahren zur Beilegung von Streitigkeiten über die Interpretation und Anwendung der Regelungen Bestandteil solcher Verträge. Zunehmend verdrängen dabei juridifizierte Verfahren traditionelle diplomatische Aushandlungsprozesse zur Streitbeilegung. Die Verbreitung solcher quasi-gerichtlichen Streitbeilegungsverfahren führte zu einer Debatte über eine (entstehende) internationale Rechtsherrschaft. In dieser Debatte bleibt aber unklar, welche Auswirkungen die formalen Verfahren auf das tatsächliche Verhalten von Staaten zeigen. Diese rein empirische Frage untersuchen wir durch eine Analyse des Verhaltens von OECD-Staaten in internationalen Streitfällen. Das Papier stellt die Ergebnisse von ca. 100 Streitigkeiten aus drei Sachbereichen internationaler Politik (Welthandel, Sicherheit, Umweltschutz) im Vergleich über Zeit (1970er/80er Jahre mit den 1990er Jahren) vor. Unsere Forschung zeigt, dass OECD-Staaten vermehrt internationale Streitbeilegungsverfahren nutzen und akzeptieren. Allerdings bestehen erhebliche Unterschiede zwischen den einzelnen Politikfeldern. Während sich für den Welthandel in der Tat ein klarer Verrechtlichungsschub feststellen lässt, ist die internationale Sicherheitspolitik nach wie vor weit davon entfernt. Der Bereich Umweltschutz liegt zwischen diesen Polen. Wir stellen einen Trend in Richtung judizialisierten Staatenverhaltens fest, der aber stark von dem jeweiligen Politikbereich abhängt.
Keywords: 330